Relationships between burnout, turnover intention, job satisfaction, job demands and job resources for mental health personnel in an Australian mental health service - Scanlan, Justin Newton; Still, Megan (BMC health services research, 2019)
Background Burnout and employee turnover in mental health services are costly and can have a negative impact on service user outcomes. Using the Job Demands-Resources model as a foundation, the aim of this study was to explore the relationships between burnout, turnover intention and job satisfaction in relation to specific job demands and job resources present in the workplace in the context of one Australian mental health service with approximately 1100 clinical staff. Methods The study took a cross-sectional survey approach. The survey included demographic questions, measures of burnout, turnover intention, job satisfaction, job demands and job resources. Results A total of 277 mental health personnel participated. Job satisfaction, turnover intention and burnout were all strongly inter-correlated. The job resources of rewards and recognition , job control , feedback and participation were associated with burnout, turnover intention and job satisfaction. Additionally, the job demands of emotional demands, shiftwork and work-home interference were associated with the exhaustion component of burnout. Conclusion This study is the largest of its kind to be completed with Australian mental health personnel. Results can be used as a foundation for the development of strategies designed to reduce burnout and turnover intention and enhance job satisfaction.